2022
DOI: 10.1080/2162402x.2021.2024941
|View full text |Cite
|
Sign up to set email alerts
|

MerTK-mediated efferocytosis promotes immune tolerance and tumor progression in osteosarcoma through enhancing M2 polarization and PD-L1 expression

Abstract: The poor progress of immunotherapy on osteosarcoma patients requires deeper delineation of immune tolerance mechanisms in the osteosarcoma microenvironment and a new therapeutic strategy. Clearance of apoptotic cells by phagocytes, a process termed “efferocytosis,” is ubiquitous in tumors and mediates the suppression of innate immune inflammatory response. Considering the massive infiltrated macrophages in osteosarcoma, efferocytosis probably serves as a potential target, but is rarely studied in osteosarcoma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…3A, B ). Consistent with previous reports of MERTK blockade enhancing anti-tumor response 10,12,13,21-27 , 100% of Mertk -/- V1 mice remained tumor free, compared to 0% of B6 WT control mice ( Fig. 3B ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…3A, B ). Consistent with previous reports of MERTK blockade enhancing anti-tumor response 10,12,13,21-27 , 100% of Mertk -/- V1 mice remained tumor free, compared to 0% of B6 WT control mice ( Fig. 3B ).…”
Section: Resultssupporting
confidence: 92%
“…An important, newly discovered role of MERTK is as an innate immune checkpoint in cancer 10,12,13,21-27 . Mertk -/- V1 mice were used to demonstrate improved anti-tumor immune response against MMTV-PyVmT, B16:F10 and MC38 tumor models 10 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that efferocytosis not only facilitates the proliferation, invasion, metastasis, and angiogenesis of tumor cells, but also affects the drug resistance to anti-cancer treatments (Birge et al, 2016;Barkal et al, 2018;Barkal et al, 2019;Tajbakhsh et al, 2021). Recently, Lin et al reported that MERTK-mediated efferocytosis promotes immune tolerance and tumor progression in osteosarcoma through enhancing M2 polarization and programmed death ligand-1 expression (Lin et al, 2022). Furthermore, an excellent study revealed that blockade of phagocytic receptor MERTK on tumorassociated macrophages augmented tumor immunogenicity and potentiated anti-tumor immunity via inducing tumor-cGas and host-STING-dependent type I interferon response (Zhou et al, 2020).…”
Section: Cancermentioning
confidence: 99%